Meningkatkan Keaktifan Belajar Siswa Kelas XI-5 SMAN 2 Kupang Melalui Media Wordwall - Adu, Aron Fresli; Nai, Firmina Angela; Pono, Chatrina (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2024)
The problem in this research is the lack of student activity in learning. This research aims to see whether Wordwall can increase student learning activity. This study was carried out in 3 cycles by increasing various efforts to increase learning activity. The subjects studied were 30 students in class XI-5 at SMA Negeri 2 Kupang. Observations, activity sheets, and documentation are sources of research data. The results show that the eight indicators from cycles 1 to 3 show an increase in students' learning activeness, in cycle one the average number is 14.3 with a percentage of 42 percent, in cycle two the average number is 16.8 with a percentage of 52.5 percent and in cycle 3 the number an average of 18.5 with a percentage of 57.9 percent. Wordwall has proven successful as a medium for increasing student participation, student activity in learning, and their interest in lessons. It also allows you to create a more interactive and engaging learning environment.